Performance evaluation of brinjal genotypes in the mid-hill region of Gandaki Province, Nepal - Lohani, Santosh; Aryal, Lok Nath; Aryal, Sunil; Adhikari, Saroj; Bhusal, Yubraj (Nepal Agriculture Research Journal, 2023)
Six genotypes of brinjal were evaluated at the Horticulture Research Station, Malepatan to identify the potential genotype for mid-hills of Gandaki province in the month of May 2020 and 2021. Experiments were conducted in a Randomized Complete Block Design (RCBD) with four replications. The genotypes were Jumli Local, Parwanipur Selection 1, Pusa Purple Long, Tanahun Collection, Takunchaur Collection, and Pokhara Lurkee. There were significant (p<0.05) differences in the observed parameters such as fruit per plant, fruit length, fruit weight, and total yield. The highest number of fruits per plant (21.56) was found in the Tanahun Collection followed by Pokhara Lurkee (13.44). The longest fruit (16.07 cm) was found in Pokhara Lurkee, which was at par with Pusa Purple Long (15.51 cm). The highest yield (33.24 mt ha-1) was found in Tanahun Collection followed by Pokhara Lurkee (23.55 mt ha-1). Though Tanahun Collection performed better in yield, Pokhara Lurkee was preferred by the farmers and consumers of the growing area due to long cylindrical shape and its purple color. From this research, it can be concluded that there is a possibility of increasing the productivity of brinjal by the selection of high yielding and consumer preferred genotypes for mid-hill condition of Gandaki province. The genotype showing higher yield and better adaptability needs further evaluation in farmer's field conditions to check the consistency in their performance, and hence, register as a variety.